Primary cardiac Burkitt-like lymphoma of the right atrium - Legault, Sylvie (Pulsus Group Inc, 2009)
A 74-year-old man presented for shortness of breath. Echocardiography revealed the presence of a large pericardial effusion with signs of tamponade. A right atrial mass was suspected and later confirmed by transesophageal echocardiography. The mass was attached to the right side of the interatrial septum. Surgical resection was performed. Histology was compatible with a diagnosis of undifferentiated B-cell non-Hodgkin’s (Burkitt-like) primary cardiac lymphoma. The present report provides the first description of a Burkitt-like primary cardiac lymphoma. The presence of a mass in the right atria should raise the possibility of a malignant cardiac tumour. Transesophageal echocardiography should be considered as the initial diagnostic procedure to be performed. Rapid histological diagnosis is important because systemic therapy can influence prognosis in the presence of a primary cardiac lymphoma.